2008
DOI: 10.1123/jpah.5.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Stress, and Metabolic Risk Score in 8- to 18-Year-Old Boys

Abstract: Background:We examined whether physical activity modifies the relationship between stress and the metabolic risk score in 8-to 18-year-old males (n = 37). Methods: Physical activity (PA) and television (TV)/videogame (VG) use were assessed via accelerometer and questionnaire, respectively. Stress was determined from self-report measures. A metabolic risk score (MRS) was created by summing age-standardized residuals for waist circumference, mean arterial pressure, glycosylated hemoglobin, and high-density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…34 Studies in children show conflicting results, 23 and are limited in number, sample size, and scope of parameters studied (e.g. to a single serum cortisol sample 18,22 or to questionnaire data alone 19,35 ). For example, school-related stressful events were positively associated with visceral and subcutaneous adipose tissue in peri-pubertal Latino girls with high CAR, and not in girls with low CAR, 20 but laboratory assessment for MetS was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…34 Studies in children show conflicting results, 23 and are limited in number, sample size, and scope of parameters studied (e.g. to a single serum cortisol sample 18,22 or to questionnaire data alone 19,35 ). For example, school-related stressful events were positively associated with visceral and subcutaneous adipose tissue in peri-pubertal Latino girls with high CAR, and not in girls with low CAR, 20 but laboratory assessment for MetS was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…19 Holmes et al developed a MetS risk zscore based on blood pressure, HDL-C, hemoglobin A1c, and waist circumference in 37 boys. 42 PA was estimated from 4-days of accelerometry. The correlations between total, moderate, vigorous PA and the MetS score were low (r~-0.09 to -0.13), but in a favorable direction.…”
Section: Habitual Physical Activitymentioning
confidence: 99%
“…9 One study of 37 boys found that trait anxiety, but not perceived stress or depressive symptoms, was related to higher metabolic risk scores, defined as standardizing and summing waist circumference, mean arterial blood pressure, hemoglobin A1c, and HDL-C. 10 This study is limited because of its small sample size of boys only (no race reported) and simple correlation analyses. Räikkönen et al 11 reported that high hostility predicted participants who were classified with the metabolic syndrome three years later, compared to individuals who did not have the metabolic syndrome at either visit.…”
Section: Introductionmentioning
confidence: 97%